Improving Spatial Ability Using GeoGebra and Kahoot-Assisted Guided Discovery Learning Models - Annisa Husnul Haq. MY; Yaya Sukjaya Kusumah; Fatin Nasywa Kirana (FKIP Universitas Lampung, 2026)
At the school level, the material presented in mathematics learning includes various types, such as geometry, statistics, algebra, and arithmetic. Among these branches, geometry particularly requires strong spatial abilities, as students are expected to visualize, interpret, and mentally manipulate objects. Students' spatial abilities remain relatively low. However, a literature review on spatial ability revealed a multiplicity of spatial taxonomies and analytical frameworks that lack convergence, presenting a confusing terrain for researchers to navigate. Spatial ability refers to an individual’s capacity to form, transform, represent, and recall non-verbal information that is visual or symbolic in nature. However, in practice, many students still demonstrate relatively low spatial skills, which can hinder their understanding of mathematical concepts and problem-solving processes. Therefore, innovative learning strategies and technological support are needed to help students improve these abilities. One alternative is to integrate interactive learning media, such as GeoGebra 3D Calculator and Kahoot, into mathematics instruction. This study aimed to analyze improvements in students’ spatial abilities through the implementation of the Guided Discovery Learning model, assisted by GeoGebra and Kahoot. The research employed a quantitative approach with a quasi-experimental design. The findings revealed that implementing the Guided Discovery Learning model, supported by GeoGebra and Kahoot, significantly improved students’ spatial abilities. The use of GeoGebra 3D Calculator enabled students to visualize three-dimensional mathematical objects more clearly, while Kahoot increased students’ engagement and motivation during the learning process through interactive activities. In addition, the guided discovery approach encouraged students to actively explore concepts, construct their own understanding, and develop critical thinking skills. Overall, the integration of guided discovery learning with interactive technology media positively affected not only students’ cognitive achievement but also their affective aspects, such as confidence, motivation, and reduced mathematics anxiety. Keywords: geogebra, guided discovery learning, spatial ability.